Happy city evaluation in the new town of Fooladshahr in order to sustainable urban neighborhoods - Najmehsadat Sajad Mahabadi; Safoora Mokhtarzadeh (توسعه پایدار شهری)
Attention to happiness and its dimensions play an essential role in the desirability of the environmental quality of neighborhoods which is one of the challenges facing cities today, especially new cities. Fuladshahr is one of the first new cities in Iran in 1968 with the comprehensive and detailed plans. This city has undergone changes in recent decades and neighborhoods with many problems and difficulties such as lack of public spaces, insecurity, lack of visual beauty, lack of neighborhood facilities, environmental pollution and …  is in contradiction with the indicators of a happy city and has reduced the level of happiness and vitality of the city. The purpose of this study is to investigate the characteristics of happy city in Fuladshahr to identify the factors affecting it. In this regard, to collect information and evaluate the indicators of a happy city, a questionnaire was used and neighborhoods were ranked using TOPSIS multi-criteria decision analysis. The results of evaluation of 19 neighborhoods of Fuladshahr based on 4 dimensions of environmental, physical-functional, social and economic and its sub-criteria show that neighborhood A2 is ranked first and neighborhood C7 is ranked 19th. So that factors such as development without plan and lack of attention to urban spaces in newly established neighborhoods, identity in neighborhoods, essential land uses, beautification of neighborhoods, safety of roads, income of citizens, jobs in the city, recreational spaces and ... are effective in reducing the happiness and vitality rate of neighborhood citizens that are in low ranks. In order to improve the quality of the happy city to achieve the sustainability of Foladshahr neighborhoods, the following suggestions have been made: strengthening the infrastructure and economic potential to increase the financial capacity of households to meet basic needs, improving the quality of water spaces, creating a variety of voluntary and social activities, and preparing active street life by making happy spaces, using the identity elements of the city, let people to participate in matters related to the place of residence through neighborhood councils and public arenas.